Towards Indigenous Feminist Financial Literacy Education - Blue, Levon Ellen; Pinto, Laura Elizabeth (Journal of the Canadian Association for Curriculum Studies, 2023)
In this article, we demonstrate how current approaches to financial literacy education might benefit from the inclusion of Indigenous feminist perspectives. We argue that Indigenous feminisms can add a unique critical view of financial literacy education that may help to address shortcomings in ongoing conversations and practices in the field. In consideration of this, we offer a framework to change the mindset of educators from one of financial literacy to one of financial consciousness.